Shared decision making in cardiology: a systematic review and meta-analysis. Issue 1 (25th August 2022) - Mitropoulou, Panagiota; Grüner-Hegge, Nicolai; Reinhold, Johannes; Papadopoulou, Charikleia
Abstract : Objectives: To evaluate the effectiveness of interventions to improve shared decision making (SDM) in cardiology with particular focus on patient-centred outcomes such as decisional conflict. Methods: We searched Embase (OVID), the Cochrane library, PubMed and Web of Science electronic databases from inception to January 2021 for randomised controlled trials that investigated the effects of interventions to increase SDM in cardiology. The primary outcomes were decisional conflict, decisional anxiety, decisional satisfaction or decisional regret; a secondary outcome was knowledge gained by the patients. Results: Eighteen studies which reported on at least one outcome measure were identified, including a total of 4419 patients. Interventions to increase SDM had a significant effect on reducing decisional conflict (standardised mean difference (SMD) −0.211, 95% CI −0.316 to −0.107) and increasing patient knowledge (SMD 0.476, 95% CI 0.351 to 0.600) compared with standard care. Conclusions: Interventions to increase SDM are effective in reducing decisional conflict and increasing patient knowledge in the field of cardiology. Such interventions are helpful in supporting patient-centred healthcare and should be implemented in wider cardiology practice.